Cluster‐based coordination scheme for cooperative cognitive radio networks. Issue 9 (31st March 2015) - Tang, Yujie; Liu, Yongkang; Zhang, Ning; Mark, Jon W.; Shen, Xuemin (Sherman)
Abstract: In this paper, a cluster‐based two‐phase coordination scheme for cooperative cognitive radio networks is proposed considering both spectrum efficiency and network fairness. Specifically, candidate secondary users (SUs) are first selected by a partner selection algorithm to enter the two‐phase cooperation with primary users (PUs). In phase I, the selected SUs cooperate with PUs to acquire a fraction of time slot as a reward. In phase II, all SUs including the unselected ones share the available spectrum resources in local clusters; each of which is managed by a cluster head who participated in the cooperation in phase I. To improve the total network utility of both PUs and SUs, the maximum weighted bipartite matching is adopted in partner selection. To further improve the network performance and communication reliability, network coding is exploited during the spectrum sharing within the cluster. Simulation results demonstrate that, with the proposed cluster‐based coordination scheme, not only the PUs' transmission performance is improved, but also SUs achieve spectrum access opportunities. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this paper, a cluster‐based two‐phase coordination scheme for cooperative cognitive radio networks is proposed considering both spectrum efficiency and network fairness. Specifically, candidate secondary users are first selected by a partner selection algorithm to enter the two‐phase cooperation with primary users. Network coding is exploited during the spectrum sharing within the cluster to further improve users' performance. The results of this work indicate that our proposed cooperation scheme outperforms the traditional one.